The four-year dynamics health indicators of students universities regularly practicing hatha-yoga - Hanna Tolchieva; Hanna Dudkina; Mykhailo Dudkin (Слобожанський науково-спортивний вісник, 2016)
Purpose: to determine the dynamics of a four-year university students in health indicators, regular practice hatha-yoga. Material & Methods: the methods of theoretical analysis, synthesis and compilation of information about the study, physiological and educational testing, pedagogical experiment, methods of mathematical statistics. For experimental verification of developed on hatha-yoga program was formed by a group of 30 students enrolled in the first course of a classical university and expressed a desire for a four-year training visit this section three times a week. Age of students before the start of the experiment was 17–18 years old and they did not have special physical training. Results: it was found informative characteristics, which is possible to appreciate the level of health in the student's age. The content of training programs on hatha-yoga for university students who do not have special physical training. Experimentally tested program developed by hatha-yoga with students in universities for four years and recorded the dynamics of their health indicators. Conclusions: quantitative data of the study show the positive impact of regular exercise on hatha-yoga on the body of students. Positive dynamics is set according to the normalization of blood pressure and heart rate, improving posture, reducing excess body weight, improving physical qualities, enhancing the characteristics of the respiratory system.